Demand for central bank reserves and monetary policy implementation frameworks: The case of the Eurosystem - Pontus Åberg; Marco Corsi; Vincent Grossmann-Wirth; Tom Hudepohl; Yvo Mudde; Tiziana Rosolin; Franziska Schobert (European Central Bank (ECB), 2021)
This paper discusses commercial banks' demand for central bank reserves under two alternative monetary policy framework configurations, namely: (i) an interest rate corridor system with scarce liquidity, and (ii) a floor system with ample liquidity. It outlines the interaction between the monetary implementation framework used to steer short-term market interest rates and banks' demand for reserves. We find that by implementing a floor system, the Eurosystem has eliminated the opportunity costs of holding reserves and enabled banks to hold relatively large buffers of reserves compared with the corridor system. Additionally, the demand for reserves may have increased endogenously, as the environment of ample liquidity conditions has incentivised many banks to adapt their business models. In parallel, the demand for reserves has also increased for more exogenous reasons such as post-global financial crisis liquidity regulation and increased liquidity concentration. Our estimates indicate an increase, over recent years, in the level of excess liquidity required in the euro area to avoid a rise in short-term market rates. Moreover, the dependency on the adopted monetary policy instruments and the external environment highlights the increased uncertainty in estimating future levels of required reserves
Keywords: E41; E44; E50; E51; E58; 330; ECB; Eurosystem; central bank reserves; monetary policyimplementation; liquidity management